2011
DOI: 10.1039/c0jm03557b
|View full text |Cite
|
Sign up to set email alerts
|

Palladium nanoparticle catalysts in ionic liquids: synthesis, characterisation and selective partial hydrogenation of alkynes to Z-alkenes

Abstract: The simple heating (120 C) of Pd(OAc) 2 in 1-butyronitrile-3-methylimidazolium-N-bis(trifluoromethane sulfonyl)imide ((BCN)MI$NTf 2 ) under reduced pressure leads to the formation of stable and small-sized Pd(0)-NPs (diameter: 7.3 AE 2.2 nm). These metal nanoparticles were characterised by means of TEM, HRTEM and XPS analysis techniques. Moreover, the potential for partial hydrogenation of alkynes in multiphase systems was evaluated. The hydrogenation of internal alkynes at 25 C and under 1 bar of hydrogen yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 60 publications
4
86
0
Order By: Relevance
“…60 Further detected components were dinitrogen (m/z = 28/14), water (m/z = 18) and other components of air.…”
Section: Papermentioning
confidence: 99%
See 2 more Smart Citations
“…60 Further detected components were dinitrogen (m/z = 28/14), water (m/z = 18) and other components of air.…”
Section: Papermentioning
confidence: 99%
“…In previous works it has been shown that Pd nanoparticles are obtained by thermal decomposition of Pd(OAc) 2 in IL. 60 Furthermore, studies about the formation of ruthenium and nickel nanoparticles by decomposition of organometallic precursors in ionic liquids showed that (I) the anion plays an important role and (II) the IL itself is capable of inducing the decomposition by reaction with a complex. 9 In these cases minor amounts of IL suffered from decomposition and only traces of volatile compounds were detected in the gaseous phase, indicating decomposition of the IL.…”
Section: Synthesis Of Cu 2 O Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Surfactants, such as polymers/ dendrimers, [25][26][27][28] ligands and especially ionic liquids sufficiently shield the nanoparticles' surface and effectively prevent agglomeration. [12][13][14][15]19,29,30 Nanoparticles can be synthesised in various ways. There are several top-down and bottom-up methods with their inherent advantages and disadvantages.…”
Section: 24mentioning
confidence: 99%
“…Accordingly, ionic liquids are very popular concerning the synthesis of zero-and one-dimensional nanostructures. [4][5][6][7] Ionic liquids can act as solvents, cosolvents, [8][9][10][11] promoters, 12,13 reducing agents, [12][13][14][15] capping or protective agents and surfactants. 3,16 Despite their low melting points, ionic liquid phases show structural properties of lower order: they consist of polar and nonpolar nanoscale regimes which make them ideal templates for nanoscale synthesis.…”
Section: Introductionmentioning
confidence: 99%